Seed and seedling vigour of winged bean (Psophocarpus tetragonolobus) after single and dual inoculation with Rhizobium sp. and Bacillus cereus - Wan Mahmood, Wan Fatin Munirah; Malahubban, M.; Ab. Aziz, Zakry Fitri (Update Publishing House, 2015)
The present study was conducted to evaluate the effect of single and dual inoculation of Bacillus cereus strain UPMLH24 and Rhizobium sp. strain AM2 on seed germination and seedling vigour of winged beans (Psophocarpus tetragonolobus). Treatments were as follows: Uninoculated control, Rhizobium sp. AM2, Bacillus cereus UPMLH24, and a combination of Rhizobium sp. AM2 and B. cereus UPMLH24. Present study found that inoculation with B. cereus alone and its combination had significantly increased (p<0.05) root length, shoot length and vigour index of winged bean seedlings as compared to uninoculated control. However, present study indicated that single inoculation with B. cereus UPMLH24 was significantly higher than Rhizobium sp.AM2 +Bacillus cereusUPML24 inoculum in all parameters. In conclusion, single inoculation with Bacillus cereus UPMLH24 or in combination with Rhizobium sp. AM2 have the potential to enhance seed germination and seedling vigour of winged beans and might be suitable to be formulated as a biostimulant.